2017
DOI: 10.1002/ijgo.12205
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gestational diabetes mellitus evaluated by universal screening with a 75‐g, 2‐hour oral glucose tolerance test and IADPSG criteria

Abstract: Objective To determine the prevalence of gestational diabetes mellitus (GDM) and its association with maternal age among Turkish women diagnosed by International Association of Diabetes and Pregnancy Study Group (IADPSG) criteria. Methods A cross‐sectional study was conducted in 2013–2015 among non‐diabetic pregnant women aged 18–49 years who were universally screened for GDM by IADPSG criteria. The percentage of women meeting each diagnostic threshold and the prevalence of GDM by age group were calculated. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…According to studies performed in Turkey (25) and South Africa (26), the prevalence rate of GDM in population-based studies ranges from 11.1% to 25.8%, respectively, which is similar to the prevalence of GDM in our Chinese study for healthy women using the same diagnostic criteria. According to the National Collaborating Centre for Women's and Children's Health in the United Kingdom, the recurrence rates for gestational diabetes can reach about 85% after pregnancy (27).…”
Section: Discussionsupporting
confidence: 85%
“…According to studies performed in Turkey (25) and South Africa (26), the prevalence rate of GDM in population-based studies ranges from 11.1% to 25.8%, respectively, which is similar to the prevalence of GDM in our Chinese study for healthy women using the same diagnostic criteria. According to the National Collaborating Centre for Women's and Children's Health in the United Kingdom, the recurrence rates for gestational diabetes can reach about 85% after pregnancy (27).…”
Section: Discussionsupporting
confidence: 85%
“…Diagnosis of GDM relied on the results of OGTT that was interpreted according to the recommendations of the International association of diabetes and pregnancy study groups (20) ; similarly multiple studies used this diagnostic policy for GDM (27,28,29) . The reported figure for frequency of GDM goes in hand with Ma et al (30) , Karcaaltincaba et al (31) and Arbib et al (32) who reported frequencies of 12.2%, 11.1% and 9.9%, respectively for GDM. Moreover, Huhn et al (33) and Brown & Wyckoff (34) documented that the introduction of the IADPSG criteria resulted in an absolute increase of GDM prevalence of 8.5% (33) and a 1.03-3.78-fold rise versus baseline criteria (34) .…”
Section: Discussion:-mentioning
confidence: 81%
“…The American College of Obstetricians and Gynecologists (ACOG) and the National Institutes of Health (NIH) suggest a two-step approach, while The American Diabetes Association (ADA) has stated that any one of the one-or two-step approaches may be used. In the literature, the prevalence of GDM in our country is reported as 1.2-27.9% [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In our study, GDM screening with a single step 75g OGTT revealed that the prevalence in Kayseri was 16% according to the IADPSG criteria.…”
Section: Discussionmentioning
confidence: 61%
“…Ozdemir et al [16] prospectively researched GDM prevalence and found it to as 8.4% according to single-step screening and IADPSG criteria. The prevalence of GDM among 1434 pregnant women by Karcaaltıncaba et al [18] revealed it as 11.1% according to IADPSG criteria with single-step screening. Recently, Ozgu et al [19] found that the prevalence of GDM was 21% according to IADPSG criteria with single-step screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation